2022
DOI: 10.1088/1755-1315/1027/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

The estimated total area of forest fire in Siak Regency, Riau Province during the early period of COVID-19 outbreak

Abstract: Forest fires in Indonesia are more prominently caused by human factors rather than natural factors. In 2020, the COVID-19 outbreak resulted in social distancing policies which leads to the restriction and limitation of human activities. This research aims to compare the forest fire areas and the number of cases between the early period of the COVID-19 outbreak and the normal period before the outbreak. In this research, we used Sentinel-2 images for further analysis through visual method and Normalized Burn Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…From March to December 2020, active fires were reported decreased by 21% in US forests [14]. According to a study conducted in Siak Regency (Indonesia) using Sentinel-2 imagery, there were approximately 459.71 ha of burned areas in 2020, which is substantially less than in 2019 with 1236.8 ha [15]. The data from satellites has shown that the pandemic in Nepal has contributed to a decrease of 4.54% in the number of forest fire incidents and a decrease of 11.36% in the radiation power of fire, and the cause may be due to the restrictions on the movement of people [16].…”
mentioning
confidence: 99%
“…From March to December 2020, active fires were reported decreased by 21% in US forests [14]. According to a study conducted in Siak Regency (Indonesia) using Sentinel-2 imagery, there were approximately 459.71 ha of burned areas in 2020, which is substantially less than in 2019 with 1236.8 ha [15]. The data from satellites has shown that the pandemic in Nepal has contributed to a decrease of 4.54% in the number of forest fire incidents and a decrease of 11.36% in the radiation power of fire, and the cause may be due to the restrictions on the movement of people [16].…”
mentioning
confidence: 99%